The Meaning of the Made in Italy Changes in a Changing World - Giumelli, Riccardo (Italian Sociological Review, 2016)
The purpose of this paper is to reflect on the possibility of a change in the widespread idea of ‘Made in…’, which we all are familiar with, in relation to some values and an identity that remind us of the place where products are manufactured. In particular, we studied the case of Made in Italy, which, in the collective imagination, is connected to a production that comes from Italy according to the logic of a production characterized territorially. But in a world where the processes of globalisation, or rather of glocalisation, are deconstructing the fundamental paradigm of the nation-state and territoriality in favour of mobility, is it still possible to speak unequivocally of Made in Italy? In our paper we will discuss step by step how we are assisting in important cultural changes that can give new meaning to the globally recognized expression. We reflect on this issue starting from the most widespread theories and with reference to exemplary cases.